Prehistoric Hunter-Gatherers in the Philippines—Subsistence strategies, adaptation, and behaviour in maritime environments - Pawlik, Alfred F.; Fuentes, Riczar B. (Frontiers in Earth Science, 2023)
Archaeological research in the Philippines has produced a timeline of currently over 700,000 years of human occupation. However, while an initial presence of early hominins has been securely established by several radiometric dates between 700-1000ka from Luzon Island, there is currently little evidence for the presence of hominins after those episodes until c. 67-50ka for Luzon or any of the other Philippine islands. At around 40ka, anatomically modern humans had arrived in the Philippines. Early sites with fossil and/or artefactual evidence are Tabon Cave in Palawan and Bubog 1 in Mindoro Occidental, the latter situated in the Wallacean part of the archipelago. This paper presents an overview of the archaeological research on the prehistory of the Philippines which has significantly intensified over the past 20 years and is providing a variety of evidence for the successful adaptation of those first islanders to maritime environments, the diversity of technological and subsistence strategies, and increasingly complex interrelationships across Island Southeast Asia.